Assessment scales for obsessive–compulsive disorder. (June 2011) - Storch, Eric A; Benito, Kristen; Goodman, Wayne
SUMMARY  Numerous assessment scales have been introduced in the obsessive–compulsive disorder (OCD) literature. Such scales have considerable clinical utility because OCD is often misdiagnosed and there is a need to monitor treatment course and response. This article briefly reviews adult OCD assessment scales, specifically clinician-administered interviews and patient-report measures. The manuscript concludes with a discussion of future directions.